Pengenalan Konsep Fisika dalam Kehidupan Sehari-hari bagi Kelompok Anak di Sentani sebagai Upaya Meningkatkan Minat dan Pemahaman Sains - Flinn C. Radjabaycolle; Martina Bunga; Rachmadani O. Susilowati; Veronince Kogoya; Julio E. P. Webori (JURNAL PENGABDIAN PAPUA, 2026)
Physics plays an essential role in everyday life; however, it is often perceived as difficult and abstract, particularly by elementary school students. This community service program was conducted at SD Negeri Inpres Kleublouw, Jayapura Regency, to introduce basic physics concepts through simple, low-cost, and interactive experiments. The program aimed to improve students’ understanding of fundamental principles such as force, balance, load distribution, inertia, and air pressure, while fostering curiosity and interest in science. The activities involved fourth-, fifth-, and sixth-grade students and were implemented through demonstrations, educational games, and interactive discussions. Three experiments were conducted: paper tower structures to explore compressive force distribution and stability, paper bridges to demonstrate the effect of shape on rigidity and load-bearing capacity, and a ruler-and-paper experiment to illustrate air pressure and material strength. The results showed high student enthusiasm and active participation. Students demonstrated improved conceptual understanding and greater interest in physics. The program also provided valuable pedagogical experience for university students and offered teachers practical examples of experiment-based science instruction using simple materials. Overall, the initiative highlights that interactive, hands-on activities can effectively enhance science literacy in elementary schools, particularly in resource-limited settings